Pentaksiran berasaskan sekolah dalam KSSR : persepsi, amalan dan masalah guru di daerah Kluang - Thangamani, Elansegaran (2013)
This study aims to identify the perceptions, practices and problems in the implementation of the School-Based Assessment (SBA) in the Standard Curriculum for Primary School (SCPC) in Kluang, Johor. The questionnaire which consists of four sections was used as instrument in this study . The sample consisted of 267 teachers from 20 Primary Schools in Kluang, Johor. Computer program SPSS Version 20.0 was used to analyze the data . The results showed that the perceptions, practices and problems have high mean values with each having a mean value of 3.93, 3.84 and 3.95 respectively. Perceptions of teachers who teach in urban schools do not differ from teachers teaching in rural schools, but in terms of practices and problems, the teachers in urban schools have higher mean values. The mean values for practices and problems of teachers who teach in urban schools are 4.01 and 3.93 respectively. This indicates that teachers in urban schools have problems in the implementation of SBA in SCPC. In addition, teachers teaching more than 10 years had a higher mean value in terms of perceptions, practices and problems of SBA in the SCPC with a mean of 4.09, 4.06 and 3.96 respectively. Their mean values are higher compared to those who teach less than 10 years. The study also shows that there are significant differences between aspects of perception, practices and problems with teaching experiences among teachers. In addition, there are also significant differences between practices and problems with the schools category. However, there is no significant difference between the perceptions of teachers with the categories of schools. Overall, perceptions, practices and problems of implementation of SBA in the SCPC, among the teachers in Kluang at a high level